Transumbilical laparoendoscopic single-site surgery vs. multiport laparoscopic surgery for benign ovarian cysts: a retrospective cohort study - Shuzhi Shan; Sufen Zhao; Xiao Wang (BMC Surgery)
Abstract Background Transumbilical laparoendoscopic single-site surgery (TU-LESS) has gained increasing attention due to the potential to maximize the benefits of laparoscopic surgery. This study aimed to compare outcomes of TU-LESS and multiport laparoscopic surgery (MLS) for the treatment of benign ovarian cysts. Methods This retrospective cohort study included patients with benign ovarian cysts that were admitted to the Second Hospital of Hebei Medical University between September 2010 and September 2022. Inverse probability of treatment weighting (IPTW) approach weighting were used to compare outcomes of TU-LESS and MLS for benign ovarian cysts. The primary outcome was the rate of cystic content spillage. Results A total of 528 patients with benign ovarian cysts were included and 236 (44.6%) patients underwent TU-LESS. The risk of cystic content spillage [relative risk (RR) = 4.37, 95% confidence interval (CI): 2.59–7.38), P < 0.001] and operation time (β = 4.94, 95% CI: 1.40–8.48, P = 0.017) during TU-LESS was significantly higher than that during MLS. While hospital stay (β=-0.10, 95% CI: -0.198 - -0.004, P = 0.043) during TU-LESS was significantly shorter. IPTW analyses yielded similar patterns of results. For ovarian cysts < 10 cm, the risk of cystic content spillage, operation time and EBL during TU-LESS was significantly higher than that during MLS (all P < 0.05). On the contrast, for ovarian cysts ≥ 10 cm, the risk of cystic content spillage, operation time and EBL during TU-LESS was significantly lower than that during MLS (all P < 0.05). Conclusions TU-LESS had a significantly higher risk of cystic content spillage, longer operation time than MLS. While for ovarian cysts ≥ 10 cm, TU-LESS had a lower risk of cystic content spillage, shorter operation time, and less EBL than MLS. More experienced surgeons are needed to perform TU-LESS in benign ovarian cysts.